Targeting DNA vaccines to myeloid cells using a small peptide. Issue 1 (2nd November 2014) - Ye, Chunting; Choi, Jang Gi; Abraham, Sojan; Shankar, Premlata; Manjunath, N.
<x xml:space="preserve">Abstract</x> Targeting DNA vaccines to dendritic cells (DCs) greatly enhances immunity. Although several approaches have been used to target protein Ags to DCs, currently there is no method that targets DNA vaccines directly to DCs. Here, we show that a small peptide derived from the rabies virus glycoprotein fused to protamine residues (RVG‐P) can target DNA to myeloid cells, including DCs, which results in enhanced humoral and T‐cell responses. DCs targeted with a DNA vaccine encoding the immunodominant vaccinia B8R gene via RVG‐P were able to restimulate vaccinia‐specific memory T cells in vitro. Importantly, a single i.v. injection of B8R gene bound to RVG‐P was able to prime a vaccinia‐specific T‐cell response that was able to rapidly clear a subsequent vaccinia challenge in mice. Moreover, delivery of DNA in DCs was enough to induce DC maturation and efficient Ag presentation without the need for adjuvants. Finally, immunization of mice with a DNA‐vaccine encoding West Nile virus (WNV) prM and E proteins via RVG‐P elicited high titers of WNV‐neutralizing Abs that protected mice from lethal WNV challenge. Thus, RVG‐P provides a reagent to target DNA vaccines to myeloid cells and elicit robust T‐cell and humoral immune responses.